Using Demographic Variables to Understand Body Size Perception and Implications for Retailers. (1st December 2017) - Alexander, Marina; Pisut, Gina; Ivanescu, Andrada E.
Abstract : The purpose of the study was to identify demographic variables associated with women's body mass index (BMI) and body size perceptions and to determine if BMI affects body size perception. SizeUSA data ( n = 6, 811) were used for the data analysis. A multinomial regression between demographic variables, BMI, and body size perception showed that each demographic variable was a significant predictor of a women's BMI and body size perception. Results can be used to understand the BMI and body size perceptions of female consumers. Retailers can use the results to customize merchandise assortments for each store based on their target market's demographics.